Ecoliteration Ability of Studens in Elementary Schools: Systematic Literature Review - Irma Yulianti Budi Safitri; Muhammad Asip; Yeni Rakhmawati; Handara Tri Elitasari (Al-Aulad: Journal of Islamic Primary Education, 2023)
Ecoliteracy lessons have been given to students, but in reality there has been no improvement in awareness of the environment. For example, students still throw garbage carelessly. Ecoliteracy is a means of making students aware of the importance of maintaining environmental balance. The research aims to find the right method or model in teaching ecoliteracy skills in elementary schools (SD). This type of research is literature study. The research subject is a form of elementary school students' awareness of the importance of protecting the environment. While the research data collection method uses the PRISMA method. Meanwhile, the research data collection instrument used a systematic literature review (SLR) which consisted of identifying, evaluating and interpreting the results of previous studies. Sources of research data from Scopus and Eric articles. The data were analyzed using the quality assessment method, namely analyzing article data that is in accordance with ecoliteracy learning in elementary schools. The results of the study found that there were 8 articles, namely: 1) one article problem solving model, 2) two article teaching materials, 3) two article contextual learning, 4) one project-based model, 5) one article adiwiyata school, 6) one article technology. Based on the research findings, it can be concluded that ecoliteracy research specifically discusses ecoliterate learning models in elementary schools, only three articles. In the process of learning ecoliteracy in elementary school, it is necessary to develop a special model for learning ecoliteracy in elementary school.Keywords: Ecoliteration, Elementary Schools